Delivering Trust: How Food Safety Performance Drives Loyalty Across The Online Ordering Journey - (:unkn) unknown (Emerald Publishing Limited, 2024)
Purpose This research delineates the interdependencies between e-service quality (e-SQ), product quality (PQ) and food biosafety measures (FBM) in shaping consumer satisfaction and loyalty within the online food delivery services (OFDS) landscape. Anchor...
Keywords: Seguridad alimentaria; Lealtad del consumidor